Cellular immunotherapy on primary multiple myeloma expanded in a 3D bone marrow niche model. (3rd June 2018) - Braham, Maaike V. J.; Minnema, Monique C.; Aarts, Tineke; Sebestyen, Zsolt; Straetemans, Trudy; Vyborova, Anna; Kuball, Jurgen; Öner, F. Cumhur; Robin, Catherine; Alblas, Jacqueline
ABSTRACT: Bone marrow niches support multiple myeloma, providing signals and cell-cell interactions essential for disease progression. A 3D bone marrow niche model was developed, in which supportive multipotent mesenchymal stromal cells and their osteogenic derivatives were co-cultured with endothelial progenitor cells. These co-cultured cells formed networks within the 3D culture, facilitating the survival and proliferation of primary CD138 + myeloma cells for up to 28 days. During this culture, no genetic drift was observed within the genomic profile of the primary myeloma cells, indicating a stable outgrowth of the cultured CD138 + population. The 3D bone marrow niche model enabled testing of a novel class of engineered immune cells, so called TEGs (αβT cells engineered to express a defined γδTCR) on primary myeloma cells. TEGs were engineered and tested from both healthy donors and myeloma patients. The added TEGs were capable of migrating through the 3D culture, exerting a killing response towards the primary myeloma cells in 6 out of 8 donor samples after both 24 and 48 hours. Such a killing response was not observed when adding mock transduced T cells. No differences were observed comparing allogeneic and autologous therapy. The supporting stromal microenvironment was unaffected in all conditions after 48 hours. When adding TEG therapy, the 3D model surpassed 2D models in many aspects by enabling analyses of specific homing, and both on- and off-target effects, preparing the ground for the clinical testing of TEGs. The model allows studying novel immunotherapies, therapy resistance mechanisms and possible side-effects for this incurable disease.